Conservation Of Juwet (Syzygium Cumini) Plant Using In Vitro Culture Techniques - Ummah, Maslahatul; Mashluhah, Kholidatul; Resmisari, Ruri Siti (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2019)
Juwet (Syzygium cumini) Â is a plant that has benefits as a medicine for type II diabetes mellitus, lungs, coughing, laxative urine. However, juwet is a scarce plant, it needs cultivation as a form of cuonservation. One of them is by utilizing biotechnology, which is of plant tissue culture. This study aims to determine the effect of the combination of 2,4-D and BAP growth regulators on the growth of juwet embryonic callus and the effect of the combination NAA and BAP on the growth of axillary bud juwet as a conservation effort. This research is experimental. Using a Completely Randomized Design (RAL) with combination 2,4-D (0; 0.5; 1; 1.5; 2; 2.5; 5) mg/L, and BAP (0; 0.25; 0.5; 0.75; 1) mg/L and combination NAA (0; 0.25; 0.5; 0.75; 1) mg/L and BAP (0; 0.5; 1; 1.5; 2) mg/L. Analysis by Two Way ANAVA test Î± = 5%. If there is a significant difference, the Duncan Multiple Range Test (DMRT) test with a significant level of 5%. Addition of 2.5 mg/L and 3 mg/L 2.4-D without BAP can induce intermediate callus, brownish yellow and there is a large cell nucleus in each cell. While the results of axillary bud growth is treatment in BAP 1 mg/L without NAA is the most effective interaction on the emergence of buds is 26.6 days after planting with the total of buds as much as 6.66, and the highest buds 5.37 cm and the highest total of leaves, namely 8.33 strands.Â